Belajar Bahasa Arab dengan Online Self Access Learning - Suwito Suwito (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
nowadays, internet becomes worldwide life style. E-mail, chatting, sites, web, blog, and other electronic terms like e-book, e-learning, e-journal, become an inseparable part of life. Electronic—especially internet—has great impact on civilization, positive and negative. At education domain, internet can become supporting, obstacle, or even depraving factor. As a learning and education media, internet offer more flexible autodidact learning. Many variation offered by sites that concentrated on Arabic language learning. Online self-learning can increase student enthusiasm, even have to be supported by other education aspect in order to reach successful learning.